2018
DOI: 10.1016/j.diamond.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal effects during nanodiamond synthesis from a carbon aerogel in a laser-heated diamond anvil cell

Abstract: Nanodiamonds have emerged as promising materials for quantum computing, biolabeling, and sensing due to their ability to host color centers with remarkable photostability and long spincoherence times at room temperature. Recently, a bottom-up, high-pressure, high-temperature (HPHT) approach was demonstrated for growing nanodiamonds with color centers from amorphous carbon precursors in a laser-heated diamond anvil cell (LH-DAC) that was supported by a near-hydrostatic noble gas pressure medium. However, a deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Unlike ion implantation, which requires annealing to drive vacancy diffusion to activate incorporated heteroatoms, optically active color centers form immediately upon HPHT conversion to diamond. Theoretical and experimental results show that, at these pressures, subnanometer sp 3 carbon grains nucleate at each aerogel grain’s core and diamond growth with simultaneous Ostwald ripening continues radially ( 15 , 41 , 42 ). The production of homogeneously distributed defects suggests that, as the diamond lattice forms around the heteroatomic silicon and nitrogen atoms, the lowest-energy color center structure forms immediately.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike ion implantation, which requires annealing to drive vacancy diffusion to activate incorporated heteroatoms, optically active color centers form immediately upon HPHT conversion to diamond. Theoretical and experimental results show that, at these pressures, subnanometer sp 3 carbon grains nucleate at each aerogel grain’s core and diamond growth with simultaneous Ostwald ripening continues radially ( 15 , 41 , 42 ). The production of homogeneously distributed defects suggests that, as the diamond lattice forms around the heteroatomic silicon and nitrogen atoms, the lowest-energy color center structure forms immediately.…”
Section: Discussionmentioning
confidence: 98%
“…The results also elucidate the basic properties and mechanistic pathways that affect the facile (hydro)carbon-to-diamond conversion, including the diamond-like structures and bonding, as well as quaternary carbon atoms that enable a swift conversion. The facile synthesis of diamond suggests a promising use of diamondoids for investigating light-emitting defects in diamonds, which is of interest in the fields ranging from quantum technologies to biological sciences (30)(31)(32). Doped or functionalized with targeted defect elements, these energy-and time-efficient precursors can lead to better understanding and discovery of color center-containing diamonds.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been demonstrated that color centers can be introduced within diamond materials using a wide range of molecular precursors including silicic acid (SiOH 4 ), [ 165,199 ] tetraethylorthosilicate (Si(OCH 2 CH 3 ) 4 ), [ 138 ] and also a mixture of naphthalene (C 10 H 8 ) with tetrakis(trimethylsilyl)silane (C 12 H 36 Si 5 ). [ 200 ] A range of different HPHT techniques may be used including a laser‐heated diamond anvil‐cell (DAC), [ 138,165,199 ] a multi‐anvil press , [ 201 ] a toroid press, [ 200 ] and more recently a resistively‐heated DAC followed by ion‐irradiation and thermal annealing. [ 202 ] HPHT techniques have also been demonstrated to incorporate noble‐gas point defects within nanodiamond materials.…”
Section: Semiconductor Laser Coolingmentioning
confidence: 99%